Severe Genu Recurvatum Deformity Treated with Primary Rotating Hinge Replacement: A report of 2 cases - Chulsomlee, MD, Kulapat; Kulachote, MD, Noratep; Wongsak, MD, Siwadol; Chanplakorn, MD, Pongsthorn; Sa-ngasoongsong, MD, Paphon; Suphachatwong, MD, Chanyut; Kawinwonggowit, MD, Viroj (Journal of Southeast Asian Orthopaedics, 2022)
Introduction: Osteoarthritis in severe genu recurvatum associated with quadriceps weakness is one of the most challenging problems in total knee arthroplasty. The recurrent recurvatum deformity after knee replacement can be prevented by using rotating hinge knee prosthesis (RHK). However, the implant survivorship and performance of knee function after surgery are not well documented. Materials and Methods: We reported the early clinical and radiographic outcomes of end-stage severe genu recurvatum arthritis associated with quadriceps weakness treated with RHK in 2 patients. The initial hyperextension deformity were 35 and 42 degrees measured from sagittal weight bearing radiograph. The follow-up time was 18 months. Results: Quadriceps muscle strength at the last follow up were 36% and 126% above the preoperative baseline. Modified Time Up and Go test was improved from 31.06 to 18.26 seconds at 18 months follow-up in one patient. Both patients showed significant improvement in WOMAC knee score and Knee Society Score at the last follow-up. There were neither radiographic signs of implant loosening nor recurrent deformity in both patients. Conclusion: The quadriceps muscle strength can be improved even in preexisting neuromuscular disorder. Primary RHK can be used as salvage procedure for severe genu recurvatum arthritis with quadriceps weakness from neuromuscular disorder.